Pengaruh Kadar Air Awal, Kemasan dan Lama Simpan terhadap Protein Membran Dalam Mitokondria Benih Kedelai - Aurellia Tatipata (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2008)
The research aimed at studying the effect of moisture content, package and storage period on mitochondrial inner membrane protein of soybean seed. The research was conducted in the laboratory of Seed Technology and Microbiology of Gadjah Mada University from May 2002 to August 2003. A Randomized Complete Block Design was used in the experiment with three factors and three replications. The first factor was moisture content consisted of three levels, i.e. 8%, 10%, and 12%. The second was three kinds of packages namely polyethylene plastic, wheat and aluminium foil. The third was the storage period, i.e. 0, 1, 2, 3, 4, 5 and 6 months. Data collected were analyzed by analysis of variance and Duncan Multiple Range Test. Regression and correlation analysis were done to study the correlation between germination, vigor and protein content of mitochondria inner membrane. Record was made on protein content of mitochondrial inner membrane and its electrophoresis profile, electrical conductivity, germination and vigor. The result showed that moisture content, packaging and storage period had significant influences on protein content of the mitochondria inner membrane and its electrophoresis profile. Inner membrane protein of mitochondrial had a positive correlation with germination and vigor. It was concluded that moisture content, package and storage period affected inner membrane protein content of mitochondria and its protein electrophoresis profile. The protein content of mitochondrial inner membrane, germination and vigor of soybean seed stored in aluminium foil sack at 8%, 10% and 12% moisture content did not decreased within 6 months. Cell membrane damage affected mitochondrial damage.   Key words:  Soybean seed, mitochondria inner membrane protein